Dual gold(I)-catalyzed cyclization of dialkynyl pyridinium salts: [inside cover] - Tšupova, Svetlana; Cadu, Alban; Stuck, Fabian; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (ChemCatChem, 2017)
The Cover depicts our research as the final task of Ulysses. The golden bow represents the gold catalyst IPrAuNTf2, also present in the golden flasks, which operates the initial cyclization. Just as Ulysses had to shoot the arrow through the axes, here the two Pd axes are atop a black Pd/C mound to symbolize the regio- and chemoselectivity of the two sequential hydrogenations. The arrows remain in the final product to show that the hydrides are all added synfacially. In their Full Paper, Tšupova, Cadu et al. demonstrate that the overall reaction can be conducted in one pot, with two metal catalysts over three reaction steps, to cyclize and reduce the pyridinium salts to free hexahydropentalenopyridines. Cover designed by Dr. Svetlana Tšupova. More information can be found in the Full Paper by Tšupova, Cadu et al. on page 1915 in Issue 11, 2017 (DOI: 10.1002/cctc.201700018).